Complex transboundary movements of marine megafauna in the Western Indian Ocean. (10th March 2019) - Barkley, A. N.; Gollock, M.; Samoilys, M.; Llewellyn, F.; Shivji, M.; Wetherbee, B.; Hussey, N. E.
Abstract: Transboundary marine species have an increased risk of overexploitation as management regimes and enforcement can vary among states. The complex geopolitical layout of exclusive economic zones (EEZs) in the Western Indian Ocean (WIO) introduces the potential for migratory species to cross multiple boundaries, consequently a lack of scientific data could complicate regional management. In the current study, we highlight both the relative lack of spatial data available in the WIO, and the prevalence of transboundary movements in species that have previously been studied in the region. Five tiger sharks Galeocerdo cuvier were tracked with near real‐time positioning (SPOT) satellite tags to determine individual shark movements relative to EEZs within the WIO. Concurrently, a literature search was performed to identify all satellite telemetry studies conducted to date in the WIO for marine megafaunal species, and the results compared to global satellite telemetry effort. Finally, the satellite tracks of all marine species monitored in the WIO were extracted and digitized to examine the scale of transboundary movements that occur in the region. Tiger sharks exhibited both coastal and oceanic movements, with one individual crossing a total of eight EEZs. Satellite telemetry effort in the WIO has not matched the global increase, with only 4.7% of global studies occurring in the region. Species in the WIO remained within the EEZ in which they were tagged in only three studies, while all other species demonstrated some level of transboundary movement. This study demonstrates the lack of spatial data available for informed regional management in an area where transboundary movements by marine megafauna are highly prevalent. Without more dedicated funding and research, the rich biodiversity of the WIO is at risk of overexploitation from the diverse threats present within the various political regions. Abstract : Transboundary marine species have an increased risk of overexploitation as management regimes and enforcement can vary among states. The complex geopolitical layout of exclusive economic zones (EEZs) in the Western Indian Ocean (WIO) introduces the potential for migratory species to cross multiple boundaries, and consequently a lack of scientific data could impede regional management. In this study, we highlight both the relative lack of spatial data available in the WIO, and the prevalence of transboundary movements in those species that have been studied to date.